Health risk assessment of heavy metals on PM2.5 in Tehran air, Iran - Anoushiravan MohseniBandpi; Akbar Eslami; Mansour Ghaderpoori; Abbas Shahsavani; Ali Khani Jeihooni; Afshin Ghaderpoury; Abdolazim Alinejad (Data in Brief, 2018)
The general goal of this study was to measure the concentration of heavy metals on suspended particles and evaluate the health-risk assessment of these metals on human health. In this study, the concentration of heavy metals adsorbed on suspended particles less than 2.5 μm was determined. For determining of health-risk assessment, the developed method of USEPA was used. The health-risk assessment of carcinogen and non- carcinogen of suspended particles were evaluated in three main paths include oral ingestion, inhalation, and dermal contact. The average annual concentrations of Al, Fe, As, Cd, Cr, Cu, Mn, Ni, Pb, V, and Zn were 1.77, 1.14, 0.03, 0.02, 0.07, 0.15, 0.06, 0.03, 0.1, 0.04, and 0.14 μg/m3, respectively. Between different stations, the order for the heavy metals was followed as urban>traffic>suburban. The average risk of carcinogenic at urban stations in the spring for As, Cd, and Cr was 2.25*10−9, 2.09*10–12, and 2.05*10–11, respectively. Keywords: Air pollution, Health risk assessment, Heavy metals, Tehran